Preferences for Data Privacy: Sharing Personal Information with Close and Distant Peers - Simeon Schudy; Verena Utikal (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
We provide evidence that people have preferences for data privacy and show that these preferences partly reflect people's interest in controlling who receives their private information. Participants of an experiment face the decision to share validated personal information with peers. We compare preferences for sharing potentially embarrassing information (body weight and height) and non-embarrassing information (address data) with geographically proximate or distant peers. We find that i) participants are willing to give up substantial monetary amounts in order to keep both types of information private, ii) data types are valued differently, and iii) prices for potentially embarrassing information tend to be higher for geographically proximate than distant peers.
urn:nbn:de:bvb:19-epub-20791-6
Keywords: C91; D80; D82; 330; preferences; data privacy; information transmission; experiment